Underground utilities for construction practitioners and homeowners - Al-Bayati, Ahmed (ASCE Press, 2021)
"Authors Al-Bayati and Panzer discuss the use of utility location services and the role that all stakeholders contribute to the reduction of damages to underground utilities during construction"--